The Effect of Asymmetry Information, Budget Target Clarity, and Budget Participation on Budgetary Slack with Organizational Commitment as a Moderating Variable: A Literature Review - Pratama, Bobby; Florencia, Irene Tri; Mukhtaruddin, Mukhtaruddin (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to provide a comprehensive understanding of the budgetary slack phenomenon. The method used is a systematic literature review (SLR) of 100 journal articles published in Scopus-indexed journals (Q2–Q4) and Sinta 2 to Sinta 4 during the period 2016–2025. The results of the study indicate that agency theory is the most dominant theoretical framework used, while asymmetry information has been shown to increase the tendency of budgetary slack. Conversely, the influence of budget target clarity and budget participation still produces diverse and inconsistent findings. The differences in research results are thought to be influenced by the organizational context, the research period, and the measurement instruments used. The novelty of this study lies in the use of organizational commitment as a moderating variable. The literature shows that organizational commitment has been shown to weaken the positive effect of asymmetry information and strengthen the positive effect of budget target clarity and budget participation in reducing budgetary slack.